Dual Listing Shares and Their Cost Registration Effect - Hauser, Shmuel; Yankilevitz, Rita; Yosef, Rami (Current Aspects in Business, Economics and Finance Vol. 7, 2023)
Does the dual listing of a stock affect its share price and liquidity? To explore this question, we used an amendment to the Israeli Securities Law passed in 2000 exempting Israeli companies already trading in the US, but not in Israel, from the requirement of also reporting to the Israeli Securities Authority. As a result, more than 30 companies traded on the Nasdaq decided to list their shares on the Tel Aviv Stock Exchange as well. Our findings indicate that since that point, the volume of trade of dual listed companies has increased by about 123%. In addition, about 42% of the total volume has occurred on the Tel Aviv Stock Exchange without having a negative effect on the volume of trade on the Nasdaq. Finally, as a result, share prices have increased by about 9%. One possible implication of these results for policymakers is the positive effect of harmonized supervision such as the European Single Passport on international capital markets.